The Effect Of Urea Dosage On Growth And Yield Of Mustard Green Pakcoy (Brassica rapa L.) - kholid syarifuddin hadun; Agus Sugianto; Abdul Basit (AGRONISMA, 2022)
Green mustardÂ is a type of vegetable plant belonging to the Brassicaceae family. Nutrients that have a major role in plant growth and production are N, P, and K. Nitrogen is one of the most important nutrients for leaf growth. One of the fertilizers with a high source of N is Urea fertilizer which contains 45% N, so it is widely used by farmers in order to increase plant growth. This study aims to determine the efficiency of the dose of urea on the yield and growth of Mustard Pakchoy (Brassica rapa L.). This study used a simple randomized block design consisting of five treatments N0: 0 kg/ha urea fertilizer, N1: 100 kg/ha urea fertilizer, N2: 200 kg/ha urea fertilizer, N3: 300 kg/ha urea fertilizer, N4: 400 kg/ha of urea fertilizer treatment was repeated four times and each replication was filled with nine plants and used three plant samples. The results showed that the treatment of N3: 300 kg/ha of urea fertilizer on the growth of plant height, number of leaves and leaf area was good. Treatment of N3: 300 kg/ha of urea fertilizer and N2: 200 kg/ha of urea fertilizer gave the same good results on the yield of economic fresh weight, total fresh weight, total dry weight, and harvest index. However, the optimum yield based on the economic fresh weight was at a dose of 235.83 kg/ha.